The Effect of Market Orientation and Entrepreneurial Orientation on the New Product Development - Bate, Adisu Fanta (Marketing & Menedzsment, 2019)
THE AIMS OF THE PAPER The researches on the effect of Market Orientation (MO) and Entrepreneurial Orientation (EO) on firms’ performance have demanded much effort in marketing researches and unparalleled results have been observed depending up on the context of the studies. But, it seems that much attention has not been given to the effect of these orientations in New Product Development (NDP), applying various forms and approaches of innovation, which is the stem for the overall performance of firms. Hence, this paper aimed to identify different forms and approaches of innovation in NPD and to explain the role or effect of EO and MO on NPD with respect to these forms and approaches of innovation. METHODOLOGY Literatures published from 1980 to 2018 in various databases (Business source Premier, Scopus, Web of Science, Science Direct and Academic Search Complete) were accessed and over forty publications were synthesized using systematic literature survey. MOST IMSPORTANT RESULTS The product innovation forms and approaches such as discontinuous versus continuous, radical versus incremental, market-driven innovation versus driving-market innovation, and pure product innovation versus marketing mix-product innovation are identified. In the case of discontinuous (also called disruptive or radical) innovation and pure product innovation forms and driving-market innovation approaches, the role of EO outweighs MO in NPD and the latter may not be even useful in these cases. In contrast to MO, EO makes firms pro-active, innovative and to take risk that leads to ground breaking product innovation. On the other hand, in the case of continuous (also called incremental) innovation, and marketing-mix related product innovation forms and market-driven innovation approaches of innovation, it is MO that plays prominent role and equips firms with up to date market intelligence from customers, competitors and suppliers. Literature also adequately supports that MO makes firms competitive in the market and helps them to cope with the existing market system. RECOMMENDATIONS Both MO and EO are important for product innovation but their application and the extent of their role or contribution varies depending on the approaches and forms of product innovation adopted, and it is not the issue of being complementary to each other or not as most studies argued. Therefore, practitioners, first, need to know the approaches and forms of innovation they needed before relying either in EO or MO. This study focused on product innovation from manufacturers’ points of view but further empirical research can be done involving service sector organizations regarding the unique roles of EO and MO.